The Right to Self-Determination of the Peoples-The Case of Kashmir - Naz, Falak (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The purpose of the present research is to examine the concept of self-determination and its applicability in international law. It also examines the applicability of secession as external right of self-determination. Secession is further analysed through the emerging doctrine of remedial secession. According to this doctrine people are entitled to secede under certain conditions that’s is when internal self-determination and human rights are violated by the parent state, and no other option is available but secession. The case of Jammu and Kashmir is the focus of this research where the Kashmiris are demanding their right to self-determination and independence from the Indian state. In this scenario, the applicability of secession is examined in the backdrop of denial of autonomy and gross human rights violations. It is endeavoured through this work to highlight the fact that the right to self –determination is of utmost importance for the people to decide their political, cultural and economic future. Keywords: Self-determination, Independence, Secession, Remedial secession, International Law, Human rights, United Nations, India, Pakistan, Jammu and Kashmir,

ÖZ:Bu araştırmanın amacı, kendi kaderini tayin kavramını ve bu kavramın uluslararası hukukta uygulanışını incelemektir. Aynı zamanda bu çalışma, dış kendi kaderini tayin hakkı bağlamında ayrılma kavramını da ele almaktadır. Ayrılma kavramı, iyileştirici ayrılma doktrini çerçevesinde ayrıca incelenecektir. Bu doktrine göre, iç kendi kaderini tayin ve insan haklarının ana ülke tarafından ihlal edilmesi ve geriye başka seçenek kalmaması halinde, insanlar ayrılma hakkına sahiptir. Keşmirlilerin kendi kaderini tayin hakkı ve Hindistan devletinden bağımsızlık hakkı talep ettiği Cemmu ve Keşmir davası, bu araştırmanın ana konusunu oluşturmaktadır. Bu durumda, ayrılmanın uygulanabilirliği konusu, özerkliğin reddi ve büyük derecede insan hakları ihlali bağlamında ele alınmaktadır. Bu çalışma ile, kendi kaderini tayin hakkının insanların siyasal, kültürel ve ekonomik anlamda geleceklerini tayin edebilmeleri adına çok büyük önem taşıdığı vurgulanmaktadır. Anahtar Kelimeler: Kendi kaderini tayin, bağımsızlık, uluslararası hukuk, insan hakları, Hindistan, Pakistan, Cemmu ve Keşmir
Master of Arts in International Relations. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Political Science and International Relations, 2019. Supervisor: Assoc. Prof. Dr. Wojciech Forysinski.
Keywords: Political Science and International Relations; Self-determination; Independence; Secession; Remedial secession; International Law; Human rights; United Nations; India; Pakistan; Jammu and Kashmir